The distinction between unipolar and bipolar depression: A cognitive theory perspective - Batmaz, Sedat; Kaymak, Semra Ulusoy; Soygur, Arif Haldun; Ozalp, Elvan; Turkcapar, Mehmet Hakan (Comprehensive psychiatry, 2013)
There is very limited data about the cognitive structure of bipolar depression when compared to unipolar depression. The aim of the study was to look into the differences between unipolar and bipolar depressed patients regarding their cognitive structure in view of Beck's cognitive theory. In this study, 70 bipolar patients during a depressive episode, 189 unipolar depressed patients and 120 healthy subjects were recruited. The participants were interviewed by using a structured clinical diagnostic scale. To evaluate the cognitive structure differences, the Automatic Thoughts Questionnaire (ATQ) and the Dysfunctional Attitude Scale (DAS) were used. We found that on the mean ATQ total score, the unipolar depressed patients scored significantly higher (92.9±22.7) than both the bipolar depressed patients (73.2±24.7) and the healthy subjects (47.1±19.6), even after controlling for all confounding factors, e.g. gender, marital status, depressive symptom severity (F = 157.872, p<0.001). The bipolar depressed patients also scored significantly higher on the mean ATQ total score than the healthy controls. On the mean DAS total score, and on the mean score of its subscale of need for approval, the bipolar depressed patients scored (152.8±21.2 and 48.2±7.4, respectively) significantly higher than both the unipolar depressed patients (160.9±29.0 and 51.9±9.7, respectively) and the healthy subjects (127.9±32.8 and 40.2±12.2, respectively), even after controlling for any confounding factor (F=45.803 [p<0.001] and F=43.206 [p<0.001], respectively). On the mean score of the perfectionistic attitude subscale of the DAS, the depressed groups scored significantly higher than the healthy subjects, but they did not seem to separate from each other (F=41.599, p<0.001). These results may help enhance the understanding of the potentially unique psychotherapeutic targets and the underlying cognitive theory of bipolar depression.